Fiscal policy shocks and stock prices in the United States - Haroon Mumtaz; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2018)
This paper uses a range of structural VARs to show that the response of US stock prices to fiscal shocks changed in 1980. Over the period 1955-1979 an expansionary spending or revenue shock was associated with modestly higher stock prices. After 1980, along with a decline in the fiscal multiplier, the response of stock prices to the same shock became negative. We use an estimated DSGE model to show that this change is consistent with a switch from an economy characterised by a more active fiscal policy and passive monetary policy to one where fiscal policy was passive and the central bank acted aggressively in response to inflationary shocks.
Keywords: C5; E1; E5; E6; 330; Fiscal policy shocks; Stockprices; VAR; DSGE